2013
DOI: 10.1111/j.1741-6612.2012.00649.x
|View full text |Cite
|
Sign up to set email alerts
|

Violence against rural older women: Promoting community awareness and action

Abstract: Objectives To identify opportunities and challenges in promoting community support for rural older women experiencing intimate partner violence (IPV). Methods Using community-based participatory research principles, we engaged in an academic-community partnership to analyze the research literature, estimate IPV incidence and prevalence, ascertain professional and older IPV victim perspectives through focus groups and interviews, and develop a collaborative community response plan. This study took place from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 20 publications
0
29
0
9
Order By: Relevance
“…This particular aspect, when it comes to the need on the part of health professionals to increase their efforts at detection, may be one of the main conclusions reached by many of the papers reviewed (DeFour, 2012;Lazenbatt et al, 2013;Montero et al, 2013;Orte and Sánchez, 2012;Roberto et al, 2013a;Simmons and Baxter, 2010;Suelve et al, 2010;Tetterton and Farnsworth, 2011), but which mitigates in favour of our aim to go deeper into this particular aspect with respect to the social and healthcare circumstances involved in ageing.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…This particular aspect, when it comes to the need on the part of health professionals to increase their efforts at detection, may be one of the main conclusions reached by many of the papers reviewed (DeFour, 2012;Lazenbatt et al, 2013;Montero et al, 2013;Orte and Sánchez, 2012;Roberto et al, 2013a;Simmons and Baxter, 2010;Suelve et al, 2010;Tetterton and Farnsworth, 2011), but which mitigates in favour of our aim to go deeper into this particular aspect with respect to the social and healthcare circumstances involved in ageing.…”
Section: Resultsmentioning
confidence: 68%
“…First, various studies emphasise that this type of violence -against older women -is not reported by the victim on many of the occasions on which it is carried out (Amesberger and Haller, 2012;Lazenbatt, Devaney and Gildea, 2013;Roberto et al, 2013a). Another additional problem, as a range of the papers reviewed emphasise, is the difficulty the health professionals consulted by older female victims of intimate partner violence have in detecting its occurrence (Lazenbatt et al, 2013;McGarry, Simpson and Hinchliff-Smith, 2011;Orte and Sánchez, 2012;Roberto et al, 2013a;Simmons and Baxter, 2010).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Specifically the need to coordinate health and social services across sectors was highlighted as a necessity to improve the system's response to violence against women 49 , a finding that was reiterated with the case management and systems navigation role along with the relationship building and community engagement adaptation strategies. Community mobilization through education, awareness, and actions has been highlighted as foundational in addressing intimate partner violence 50 and was a strategy being utilized by this rural shelter. In addition to confirming previously published knowledge in the area, this study highlighted the specific ways in which one rural shelter was changing its role, and adapting to address the shift in needs of women and the community.…”
Section: Discussionmentioning
confidence: 99%
“…Spath (2003) stated the importance of social work education in training professionals on domestic violence theories and assessment tools, and developing systems to assess for and address domestic violence issues, multidisciplinary approaches, and ethical practices for sharing client information. According to Roberto et al (2013), community professionals are agreeable to working together to support victims of IPV in late life. Community professionals rely on local domestic violence agencies for leadership and support in developing a coordinated and sustainable community response plan.Another results of the study indicated high agreement with most of the irrational beliefs about family and psychological violence.…”
Section: Domestic Violencementioning
confidence: 99%